The Role Of PT Maharupa Gatra’s Marketing Communication (MARCOMM) In Increasing Sales Via Instragram Post Covid 19 - Bani Mahardhika; Wulan Furie Lenggana (Jurnal Ilmu Sosial Mamangan, 2024)
The purpose of this writing is to analyze the role of Marketing Communication at PT Maharupa Gatra using Instagram to increase turnover after the Covid 19 pandemic. Apart from that, this research aims to analyze the obstacles and solutions implemented to overcome Marketing Communication obstacles in increasing turnover at PT Maharupa Gatra. This research method uses descriptive qualitative methods. Data collection techniques use observation techniques, in-depth interviews, literature studies both print and online. The results of this research show that Marketing Communication at PT Maharupa Gatra uses Instagram social media as a tool to increase company turnover by posting promotional programs at PT Maharupa Gatra by creating interesting content so that interaction occurs with consumers and followers on PT Maharupa's Instagram social media. Gatra. By using Instagram, it is easier for companies to convey all the information intended for customers and can also save more costs in promotions, because promotions using social media can be more economical than using conventional media. So far, everything PT Maharupa Gatra has done to increase turnover using the social media Instagram is very appropriate in the current era of digitalization, and allows Marketing Communication to always innovate in increasing turnover at PT Maharupa Gatra.